Experience, Process, and Impact of Involving Informal Caregivers of People With Dementia as Public Contributors to Inform the Development of a Complex Intervention: A Mixed‐Methods Study. - Svedin, Frida; Österman Menander, Ida; Blomberg, Oscar; Brantnell, Anders; Farrand, Paul; Lückner, Theresia; Sundelin, Kristina; Turney, Joan; Åberg, Anna Cristina; Woodford, Joanne (Health Expectations, 2025)
Introduction: Public contribution is increasingly prioritised by research institutions, funding bodies, and policymakers globally. However, the evidence base for the impact of public contribution remains limited. Researchers and public contributors' experiences of such activities are also rarely reported. We worked alongside a Public Advisory Group (PAG) consisting of informal caregivers of people with dementia during a series of studies to inform the development and adaptation of a guided low‐intensity behavioural activation intervention for people with dementia (INVOLVERA). The overall aim of the current study was to explore the experience, process, and impact of involving caregivers of people with dementia as public contributors during the intervention development phase of INVOLVERA. Methods: Public contribution activities were recorded using impact logs from PAG meetings, from which public contributors' suggestions for the intervention were extracted and categorised, and the implementation rate calculated. Semi‐structured interviews were conducted with public contributors (n = 4) and researchers (n = 3), and analysed using manifest content analysis. Results: Public contributors made 158 suggestions across nine PAG meetings, with 76% of these implemented by the researchers. Analysis of interviews generated three categories: Perceived impacts, Interactions and facilitators, and Future challenges and opportunities. Interviews suggested public contribution activities positively impacted the research (e.g., improving intervention acceptability) and those involved (e.g., new knowledge and skills). Public contributors provided valuable recommendations for involving people with dementia and male caregivers in future activities. Conclusions: Findings illustrate a positive impact of public contribution activities on the research and those involved. This underscores the important role of public contribution during the development of complex interventions and further emphasises the need for comprehensive reporting on the impact of such activities. We believe this study strengthens the evidence base for public contribution and offers practical insights into fostering effective partnerships with public contributors. Public Contribution: A PAG consisting of wives and daughters (n = 4) of people with dementia worked alongside the researchers throughout the intervention development phase of the project. Contributions included (1) sense‐making and interpreting results from a series of intervention development studies, (2) co‐designing the intervention, and (3) disseminating findings, including co‐writing the current paper.